Carotid cavernous fistula due to a ruptured intracavernous aneurysm of the internal carotid artery: treatment with selective endovascular occlusion of the aneurysm. Issue 6 (1st December 2001) - Wanke, I; Doerfler, A; Stolke, D; Forsting, M
Abstract : Intracavernous carotid artery aneurysms causing a carotid-cavernous fistula (CCF) are rare. These aneurysms usually cause neurological symptoms due to gradual expansion without rupture. If they do rupture they most often lead to a CCF instead of bleeding into the subarachnoid space. A ptient is described with a ruptured intracavernous aneurysm causing a CCF resulting in acute onset of unilateral ophthalmoplegia. Selective coil embolisation of the aneurysm led to complete occlusion of the CCF with preservation of the internal carotid artery; symptoms resolved completely.